Relationship of Nurse Therapeutic Communications to Patient Family Anxiety in Emergency Instalation Room PKU Muhammadiyah Gombong Hospital - Aenalia Ikrima Fatikhah; Isma Yuniar; Putra Agina Widyasworo (Prosiding University Research Colloquium, 2022)
Background: Communication is an important aspect that must be owned by nurses in carrying out nursing care, nurses who have therapeutic communication skill will not only easily establish a relationship of trust with patients, but also can provide professional satisfaction in services to improve the quality of nursing services and the image of the hospital, therefore therapeutic communication is intended to reduce the concents of the patient’s family because the family feels that interaction with nurses is a moment for varioius infotmation to be able to deal with anxiety.Purpose: Knowing the relationship between nurse therapeutic communications on the level of anxiety of the patient’s family un the emergency room at pku muhammadiyah gombong hospital. Method: This type of research was descriptive correlative research the sample in this study was 132 respondens, the sampel was taken using accidental sampling. Data analysis and bivariate analysis using statistical test spearman rank correlation, using a nurse therapeutic communication, questionnare with 22 question items and anxiety with 20 question item. Research result: The result of the analysis showed that there was a signification relationship between nurse therapeutic. Communication and anxiety level in the emergency room at pku muhammadiyah gombong hospital (p :0.000 : p:0,034) correlation coefficient r:0,185. Conclusion: There is a relationship between nurse therapeutic communication and the level of anxiety pf the patient’s family in the emergency room at pku muhammadiyah gombong hospital. Recommendation: PKU Muhammadiyah Hospital is pround to hold an inhouse training on therapeutic communication in patients for employees, especially nurses. For the next researcher can research in another nursing room.